Kindler Syndrome - A Case Report with Review of Literature - Antony John; R Sabitha Sudharsan; Shanmugam; M Chandra Sekhar (Wolters Kluwer Medknow Publications, 2007)
Kindler syndrome is a rare autosomal recessive skin fragility disorder characterized by blistering in infancy, followed by photosensitivity and progressive poikiloderma 1 . More than 70 cases have been documented in dermatologic and pediatric journals with little emphasis on dental findings 2 . Here we report a 18 year old female patient with Kindler syndrome along with a review of literature.